Internalized stigma in psoriasis: A multicenter study - ERGUN, SAFİYE ATLAS TÜLİN (WILEY, 2017)
Internalized stigma is the adoption of negative attitudes and stereotypes of the society regarding a person's illness. It causes decreased self-esteem and life-satisfaction, increased depression and suicidality, and difficulty in coping with the illness. The primary aim of this study was to investigate the internalized stigma state of psoriatic patients and to identify the factors influencing internalized stigma. The secondary aim was to identify the correlation of internalized stigma with quality of life and perceived health status. This multicentre, cross-sectional study comprised 1485 patients. There was a significant positive correlation between mean values of Psoriasis Internalized Stigma Scale (PISS) and Psoriasis Area and Severity Index, Body Surface Area, Dermatological Life Quality Index and General Health Questionnaire-12 (P < 0.001 in all). Lower percieved health score (P = 0.001), early onset psoriasis (P = 0.016), family history of psoriasis (P = 0.0034), being illiterate (P < 0.001) and lower income level (P < 0.001) were determinants of high PISS scores. Mean PISS values were higher in erythrodermic and generalized pustular psoriasis. Involvement of scalp, face, hand, genitalia and finger nails as well as arthropathic and inverse psoriasis were also related to significantly higher PISS scores (P = 0.001). Our findings imply that psoriatic patients experience high levels of internalized stigma which are associated with psoriasis severity, involvement of visible body parts, genital area, folds or joints, poorer quality of life, negative perceptions of general health and psychological illnesses. Therefore, internalized stigma may be one of the major factors responsible from psychosocial burden of the disease.
Keywords: Dermatology Quality of Life Index; General Health Questionnaire-12; internalized stigma; psoriasis; Psoriasis Internalized Stigma Scale; PSYCHOSOCIAL CONSEQUENCES; PERCEIVED STIGMA; TURKISH VERSION; MENTAL-ILLNESS; STIGMATIZATION; EXPERIENCE; SEVERITY; RELIABILITY; VALIDITY; IMPACT